Disparate Responses of Carbonate System in Two Adjacent Subtropical Estuaries to the Influence of Hurricane Harvey – A Case Study - Hu, Xinping; Yao, Hongming; Staryk, Cory J.; McCutcheon, Melissa R.; Wetz, Michael S.; Walker, Lily (Frontiers in Marine Science, 2020)
Two adjacent estuaries in the northwestern Gulf of Mexico (Mission-Aransas or MAE, and Guadalupe-San Antonio or GE), despite their close proximity and similar extents of freshening caused by Hurricane Harvey, exhibited different behaviors in their post-hurricane carbonate chemistry and CO2 fluxes. The oligotrophic MAE had little change in post-Harvey CO2 partial pressure (pCO2) and CO2 flux even though the center of Harvey passed right through, while GE showed a large post-Harvey increases in both pCO2 and CO2 flux, which were accompanied by a brief period of low dissolved oxygen conditions likely due to the large input of organic matter mobilized by the hurricane. The difference in the carbonate chemistry and CO2 fluxes were attributed to the difference in the watersheds from which these estuaries receive freshwater. The GE watershed is larger and covers urbanized areas, and, as a result, GE is considered relatively eutrophic. On the other hand, the MAE watershed is smaller, much less populous, and MAE is oligotrophic when river discharge is low. Despite that Harvey passed through MAE, the induced changes in carbonate chemistry and CO2 flux there were less conspicuous than those in GE. This study suggested that disturbances by strong storms to estuarine carbon cycle may not be uniform even on such a small spatial scale. Therefore, disparate responses to these disturbances need to be studied on a case-by-case basis.